Systematic Literature Review of Knowledge Management in Students Based on Education Level in Indonesia - Amelia, Dina Nur; Amrozi, Yusuf; Milad, M Khusnu (ULTIMA InfoSys, 2024)
Knowledge Management (KM) is a rapidly developing concept across various disciplines and business practices. KM encompasses the collection, storage, dissemination, and utilization of knowledge to enhance learning effectiveness. This study aims to examine the implementation of knowledge management in education across different educational levels using the Systematic Literature Review (SLR) method to analyze a number of related articles. The research findings indicate that the implementation of KM is significantly more prevalent in secondary (approximately 65%) and tertiary education levels (around 70%) compared to basic education (about 30%). Key factors influencing the success of KM implementation include the availability of infrastructure, student participation, support from teachers and staff, and a learning culture that fosters collaboration.